The Impact of Bankruptcy Law and PKPU on Business Continuity and Indonesia's Economic Recovery - Nurafifah, Diah; Iskandar, Iskandar; Hidayat, Taupik; Suryani, Santi (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The problem of unpaid debts and declining liquidity poses a serious threat to business sustainability in Indonesia. Coupled with global economic uncertainty, companies are trapped in a bankruptcy or PKPU dilemma. This complicated and challenging legal process, if it fails, can trigger a wider collapse, threatening the country's economy. Therefore, the purpose of this study is to analyze the application of bankruptcy and PKPU laws, evaluate their impact on the continuity of corporate business, and measure the effectiveness of the Indonesian legal system in supporting economic recovery and maintaining the stability of the business sector. This research method uses a normative qualitative approach by analyzing laws and legal practices related to bankruptcy and PKPU. Data were collected from laws, court decisions, and literature, then analyzed descriptively, comparatively, and critically to evaluate the impact of the law. The results of this study indicate that the application of bankruptcy and PKPU laws in Indonesia has a significant impact on the continuity of corporate business. Although it provides space for companies in financial difficulty to survive, slow procedures and high costs hinder its effectiveness. The relationship between debtors and creditors plays an important role in debt restructuring, but legal uncertainty threatens a faster economic recovery. For this reason, the Indonesian legal system needs improvement to be more efficient in supporting the economic recovery of companies and economic sectors. [Permasalahan utang yang belum terbayar dan likuiditas yang menurun menjadi ancaman serius bagi keberlanjutan bisnis di Indonesia. Ditambah dengan ketidakpastian ekonomi global, perusahaan terjebak dalam dilema kepailitan atau PKPU. Proses hukum yang rumit dan penuh tantangan ini, jika gagal, dapat memicu keruntuhan yang lebih luas, yang mengancam perekonomian negara. Oleh karena itu, tujuan penelitian ini adalah untuk menganalisis penerapan hukum kepailitan dan PKPU, mengevaluasi dampaknya terhadap kelangsungan bisnis perusahaan, dan mengukur efektivitas sistem hukum Indonesia dalam mendukung pemulihan ekonomi dan menjaga stabilitas sektor bisnis. Metode penelitian ini menggunakan pendekatan kualitatif normatif dengan menganalisis undang-undang dan praktik hukum terkait kepailitan dan PKPU. Data dikumpulkan dari undang-undang, putusan pengadilan, dan literatur, kemudian dianalisis secara deskriptif, komparatif, dan kritis untuk mengevaluasi dampak hukum tersebut. Hasil penelitian ini menunjukkan bahwa penerapan hukum kepailitan dan PKPU di Indonesia berdampak signifikan terhadap kelangsungan bisnis perusahaan. Meskipun memberikan ruang bagi perusahaan yang mengalami kesulitan keuangan untuk bertahan, prosedur yang lambat dan biaya yang tinggi menghambat efektivitasnya. Hubungan antara debitur dan kreditur memainkan peran penting dalam restrukturisasi utang, tetapi ketidakpastian hukum mengancam pemulihan ekonomi yang lebih cepat. Oleh karena itu, sistem hukum Indonesia perlu ditingkatkan agar lebih efisien dalam mendukung pemulihan ekonomi perusahaan dan sektor ekonomi.]